Functionalism-Related Framework and the Influence on Language Instruction - Khafidhoh Khafidhoh (Universitas Ahmad Dahlan, 2017)
Functionalism is one of the basic ways of thinking in linguistics while the language instruction is a complex process dealing with the language use. This article aims at giving a critical review on functionalism-related function and the influence on the language instruction area. The topics covered in this article are the definitions of the general explanation of functionalism, linguistic inputs, philosophical inputs, sociolinguistic inputs, needs analysis on language instruction, and the influence of functionalism on language instruction.